2009
DOI: 10.1007/s10695-009-9369-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic gene expression in the gonad and liver of shovelnose sturgeon (Scaphirhynchus platorynchus)

Abstract: The development of a biomarker for rapid detection of intersex is desirable to researchers and fisheries managers alike. The first step is to identify a marker that has a dimorphic expression pattern. With a focus on sex-specific genes, we assessed the use of vitellogenin (vtg), forkhead box L2 (foxl2) and doublesex and mab-3-related transcription factor 1 (dmrt1) as molecular biomarkers for the identification of gender in shovelnose sturgeon (Scaphirhynchus platorynchus), a species known to have intersex indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 38 publications
3
41
1
Order By: Relevance
“…2 A), which is similar to what has been previously reported for Acipenser fulvescens [Hale et al, 2010]. This is contrary to what has been previously reported by our lab, where we found that dmrt1 was expressed at about the same levels in male and female shovelnose sturgeon [Amberg et al, 2010]. Melt curve analysis in this study indicated 2 dmrt1 products in ovaries and generally only 1 in testes.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…2 A), which is similar to what has been previously reported for Acipenser fulvescens [Hale et al, 2010]. This is contrary to what has been previously reported by our lab, where we found that dmrt1 was expressed at about the same levels in male and female shovelnose sturgeon [Amberg et al, 2010]. Melt curve analysis in this study indicated 2 dmrt1 products in ovaries and generally only 1 in testes.…”
Section: Discussioncontrasting
confidence: 52%
“…Fish were transported live to the Indiana Animal Disease Diagnostic Laboratory at Purdue University (West Lafayette, Ind., USA) where they were measured for fork length (mm), weighed (kg) and then euthanized with a lethal dose of FINQUEL MS-222 (Argent Chemical Laboratories, Inc., Redmond, Wash., USA). Sex of each fish was determined at the time of dissection and later corroborated based on histology (H&E staining as described in Amberg et al [2010]). Ovaries contained mature black eggs and testes sperm as described in Amberg et al [2010].…”
Section: Tissue Collection and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that the sex-determination system in sturgeons is ZW for female and ZZ for male (58). Sox9, dmrt1, TrA-1, and Foxl2 have been identified as biomarkers for sex determination in some sturgeons (2,3,24,26), but no biomarker has been identified in Russian sturgeons. A previous study found that the stFSHb subunit was expressed at a higher level in 3 and 4 yr old fish than in 1 yr old fish and that the expression level of stFSHb in females was significantly higher than in males (28).…”
mentioning
confidence: 99%
“…Nevertheless, evidence is accumulating to suggest that FOXL2 is an important ovarian differentiating gene. Indeed, its ovarian-specific expression is conserved in all vertebrate species studied until now [Loffler et al, 2003;Baron et al, 2004;Govoroun et al, 2004;Wang et al, 2004;Nakamoto et al, 2006;Liu et al, 2007;Rhen et al, 2007;Wotton et al, 2007;Alam et al, 2008;Ijiri et al, 2008;Oshima et al, 2008;Siegfried and Nusslein-Volhard, 2008;Nakamoto et al, 2009;Okada et al, 2009;Shi et al, 2009;Amberg et al, 2010;Moore et al, 2010;Shoemaker-Daly et al, 2010;Wu et al, 2010], and in an invertebrate species such as the pacific oyster [Naimi et al, 2009]. In addition to the function of Foxl2 in development, Foxl2 is also required for ovarian homeostasis.…”
mentioning
confidence: 99%